600-mm aperture simultaneous phase-shifting Fizeau interferometer. (August 2018) - Zhu, Wenhua; Chen, Lei; Yang, Ying; Zhang, Rui; Zheng, Donghui; Han, Zhigang; Li, Jinpeng
Highlights: A 600-mm aperture simultaneous phase-shifting Fizeau interferometer. The phase shifting is introduced using a point source array. Four independent imaging systems are used to obtain phase-shifting interferograms. Common-path configuration to ensure high-precision measurement. Abstract: In this study, a 600-mm aperture simultaneous phase-shifting Fizeau interferometer is presented. This interferometer has a special light source configuration produced by an arrangement of four identical point sources diffracted by a phase grating. With this configuration, the phase shifts are introduced between each pair of coherent beams. A 2 × 2 image lens array is designed such that four conjugated interferograms with a phase step of π/2 can be captured in a single shot using one detector, thereby realizing dynamic measurement. The experiment was carried out using the proposed interferometer with a pair of 600 mm aperture transmission flat and reference flat placed on a platform with no vibration resistance facility. The results depict a peak-valley value of λ/10 and present a real-time phase variation caused by environmental factors, which indicates that the instantaneous measurement of the phase by the proposed large-aperture interferometer provides robust results despite the presence of environmental factors such as vibration and airflow.